Boosting Competitiveness: Digital Branding of The Sreseh Mangrove Tourism Spot in Marparan Village - Rachman, Fika Hastarita; Wahyuni, Sri; Imamah, Imamah (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2024)
Tourism acts as a conduit for enhancing the economic conditions of villages located near tourist destinations. Sreseh Mangrove Tourism (WMS) inMarparan Village is a recently established tourist destination in Sampang Regency. The Tourism Awareness Group (Pokdarwis) faces various obstacles in managing and conserving nature. These factors encompass the local population’s limited level of technology skills and the absence of digital branding as a means of promotion. Digital branding is a very eﬃcient promotional tool in the current technology age due to its ability to engage with social media users rapidly. Producing captivating content is essential as it has a favorable impact on public opinion and draws people to tourist destinations. In order to tackle this issue, we have established a program aimed at improving Pokdarwis’ proﬁciency in utilizing technology for promotional purposes. This curriculum encompasses instruction, development, and support in the realm of digital branding. The program was successfully implemented, substantially enhancing participants’ proﬁciency in generating digital material. The participants’ videos were posted on Marparan Village’s Instagram page. There are potential prospects for creating a mobile application in the future that includes digital content videos, digital promotions, and a directory of rental and vacation choices.